Javanese Culture and The Horticulture Community's Resilience of Farmers in Sawangan, Ngablak, and Magelang Districts - Fransisca Iriani Roesmala Dewi (Jurnal Ilmu Pertanian Indonesia, 2026)
Magelang Regency region contains a plateau in the shape of a basin surrounded by mountains. The agroclimatic can generate enough agricultural products in sufficient quantity and quality to meet market demand. Horticultural agricultural activities in this area have the potential to improve food security and household income, considering technical, social, institutional, commercial, financial, and environmental issues. Horticultural growers were usually under pressure due to the drop in vegetable prices. The study examines the fight of independent horticultural farmers against adversity via the lens of community resilience. Community resilience includes community interests, institutional development, defense, and capacity building operations, as well as individual actions. The purpose of this study was to describe how resilient vegetable-growing communities are to food security concerns. Five villages in the Magelang Regency were affected: Klangon Hamlet in Sawangan District, Babadan Hamlet in Srumbung District, Wonolobo Hamlet, Krangean Hamlet, and Lodosewu Hamlet in Ngablak District. The thematic analysis approach was used to identify themes or characteristics related to the psychological and financial elements of vegetable producers. The resilience of the horticultural farming community in this area is built on trust in fellow farmers; there is hope for high prices to return; there is independence in weathering crop failures; and the local values of nrimo and gemi setiti are still practiced. The robustness of adaptive networks in the form of social capital, combined with excellent management of local capacities, increases the resilience of horticultural farming communities in this area. Keywords: community resilience, falling prices, local wisdom, vegetable farmers